The Original Histological Slides of Camillo Golgi and His Discoveries on Neuronal Structure - Bentivoglio, Marina; Cotrufo, Tiziana; Ferrari, Sergio; Tesoriero, Chiara; Mariotto, Sara; Bertini, Giuseppe; Berzero, Antonella; Mazzarello, Paolo (Frontiers in Neuroanatomy, 2019)
The metallic impregnation invented by Camillo Golgi in 1873 has allowed the visualization of individual neurons in their entirety, leading to a breakthrough in the knowledge on the structure of the nervous system. Professor of Histology and of General Pathology, Golgi worked for decades at the University of Pavia, leading a very active laboratory. Unfortunately, most of Golgi’s histological preparations are lost. The present contribution provides an account of the original slides on the nervous system from Golgi’s laboratory available nowadays at the Golgi Museum and Historical Museum of the University of Pavia. Knowledge on the organization of the nervous tissue at the time of Golgi’s observations is recalled. Notes on the equipment of Golgi’s laboratory and the methodology Golgi used for his preparations are presented. Images of neurons from his slides (mostly from hippocampus, neocortex and cerebellum) are here shown for the first time together with some of Golgi’s drawings. The sections are stained with the Golgi impregnation and Cajal stain. Golgi-impregnated sections are very thick (some more than 150 μm) and require continuous focusing during the microscopic observation. Heterogeneity of neuronal size and shape, free endings of distal dendritic arborizations, axonal branching stand out at the microscopic observation of Golgi-impregnated sections and in Golgi’s drawings, and were novel findings at his time. Golgi also pointed out that the axon only originates from cell bodies, representing a constant and distinctive feature of nerve cells which distinguishes them from glia, and subserving transmission at a distance. Dendritic spines can be seen in some cortical neurons, although Golgi, possibly worried about artifacts, did not identify them. The puzzling intricacy of fully impregnated nervous tissue components offered to the first microscopic observations still elicit nowadays the emotion Golgi must have felt looking at his slides.